The use of essential trace elements in the juvenile rearing of barramundi (Lates calcarifer - Fehér, Milán; Baranyai, Edina; Simon, Edina; Juhász, Péter; Csorvasi, Éva; Bársony, Péter; Stündl, László (Acta Agraria Debreceniensis, 2014)
Barramundi (Lates calcarifer L.) is a predatory fish species native in Southeast Asia and Australia. Based on the geothermal potentiality of Hungary the warm-water fish can be reared successfully. Zooplankton in the wild contains minerals in a higher concentration than the usually fed newly hatched Artemia nauplii, therefore essential trace elements, such as cobalt, zinc and manganese play an important role in the larviculture of barramundi. Cobalt is vital in trace amount for many living functions of vertebrates, however, lower number of papers are available considering the nutritional aspects. Nevertheless. improved growth performance was observed in cases of some fish species when diet was supplemented with CoCl2. Zinc and manganese are also vital for optimal growth and accordingly are investigated and applied diet supplements in aquaculture.The main aim of the recent study is to investigate the effects of cobalt, manganese and zinc on the growth performance and homogeneity of fish when a commercially available dry diet is supplemented with trace elements individually and in combined treatments. A total of 6 treatments were set in a randomized blocked design where the concentrations of the applied elements were 50 mg kg-1 for CoCl2, for ZnSO4 and for MnCl2 individually, as well as for CoCl2 along with ZnSO4 and for CoCl2 along with MnCl2 in combination. Although the production parameters of larval barramundi were positively affected by the addition of trace elements when the retention of minerals occurred through nourishment living organisms, statistically no differences were found between the treatments considering the growth performance of barramundi juveniles either when dry feed was supplemented with cobalt, manganese or zinc (p>0.05). While the use of cobalt and manganese in combined treatments produced a less uniform larvae in size and as a consequence of increased heterogeneity, survival was significantly reduced by the cannibalism, the sizes distribution of barramundi juveniles wasn’t affected by the dry diet supplementation of these elements.